Implementace Project Management Office - Majer, Luděk (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Diplomová práce popisuje problematiku projektového řízení a kancelář projektového managementu, její funkce a umístění v organizační struktuře. V první části práce (teoretická východiska) je vymezena problematika projektového řízení, kanceláře projektového managementu. Jsou popsány základní funkce a modely. V další části je analyzován současný stav, charakteristika společnosti a popis zavedeného projektového řízení. Cílem práce je vlastní návrh řešení implementace kanceláře projektového managementu a její funkce.

The diploma thesis consist of an overal view of the issue of project management and project management office topics. Also its functions and its place in an organization structure. In the first part (the theoretical part) of this work is defined the term project management and project management office. Basic functions and models are described. Next part is contains the analysis of the current state of project management in this company. The aim of this thesis is to suggest each stage of implementation of the project management office and its functions.
Implementation of Project Management Office
Keywords: projekt; projektové řízení; kancelář projektového managementu; implementace; standardy; project; project management; project management office; implementation; standards